(3GdPjd Ydi GdQhVJjf aj CNHGQ GdOhdJjfs - (3YHO GdQMef Hf ESeGYjd Hf EHQGgje GdebOSj GdOeTbqj, CHh GdbGSe, TgGH GdOjf, CHh TGeI,J (B665 (3g` s ((3eMeO Hf YKeGf Hf fYeg G ddg Hf CHj GdhaGA Hf GdYRGRi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfaQO HGdHbGA hcJH Ydi ZjQg GdRhGd LeYJ ai cJGH GdQhVJjf cKjQkG ef GdMhGOK GdhGbYg ai Ref GdOhdJjf GdfhQjI hGdUdGMjI s
(3ai eNWhW gPg GdfSNI (B" (3GdePjd Ydi GdQhVJjf(B"s
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B125s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B157 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs